FUSARIUM SOLANI SUBRETINAL ABSCESS IN A PATIENT WITH ACUTE MYELOID LEUKEMIA. Issue Volume 12:Issues 3(2018) (2018) - Schlaen, Ariel; Ingolotti, Mariana; Lorenzon, Pablo; Mancini, Jorge; Couto, Cristobal; Casanova, Maria; Kusminsky, Gustavo; Tisi Baña, Matias; Pineda, Gloria; Rima, Alejandra; Saravia, Mario
Abstract : Purpose: To report on a case of Fusarium solani subretinal abscess in a patient with acute myeloid leukemia treated with an allogenic bone marrow transplant. Methods: A 47-year-old male with a history of acute myeloid leukemia with intermediate cytogenetic risk was admitted in our hospital. The disease relapsed after two cycles of chemotherapy. He was then treated with an allogenic bone marrow transplant, with busulfan, cyclophosphamide, and thymoglobulin. One week after the procedure, a sepsis of unknown origin in neutropenia occurred. Blood cultures and sputum were negative for bacteria and fungi. At the eighth week after the procedure, the patient had acute vision loss of the right eye. Funduscopy in the right eye revealed an inferior temporal yellowish white elevated lesion of approximately 10 disk areas and superficial perifoveal and perilesional hemorrhages. Results: Vitrectomy was performed and samples from the vitreous and the subretinal abscess material were sent for analysis. Vitreous and subretinal specimens grew colonies of a fungus morphologically consistent with F. solani . Conclusion: Fusarium solani should be included in the differential diagnosis of subretinal abscesses. Abstract : A 47-year-old male patient with a diagnosis of acute myeloid leukemia, treated with an allogenic bone marrow transplant, developed a sudden vision loss in his right eye. A subretinal abscess was observed at fundoscopy. Vitreous and subretinal specimens grew colonies of a fungus morphologically consistent with Fusarium solani .